2005
DOI: 10.1038/ni1209
|View full text |Cite
|
Sign up to set email alerts
|

The nervous system and innate immunity: the neuropeptide connection

Abstract: Many neuropeptides and peptide hormones are very similar to antimicrobial peptides in their amino acid composition, amphipathic design, cationic charge and size. Their antimicrobial activities suggest they may also be directly involved in innate defense. Here we discuss recent advances in understanding how the mammalian nervous system, equipped with neuropeptides and peptide hormones with potent antimicrobial properties, might directly defend the host from microbial assault. As examples, we have chosen five we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
344
2
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 431 publications
(363 citation statements)
references
References 104 publications
15
344
2
2
Order By: Relevance
“…In a recent study, treatment with Jagged1-and Delta1-Fc fusion proteins differentially modulated the course of EAE (27). With ␥-secretase inhibitors, it has been shown that blocking the Notch pathway prevents Th1 polarization and IFN-␥ secretion (15). Administration of GSI in vivo delayed the onset of EAE and substantially reduced clinical signs (15).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, treatment with Jagged1-and Delta1-Fc fusion proteins differentially modulated the course of EAE (27). With ␥-secretase inhibitors, it has been shown that blocking the Notch pathway prevents Th1 polarization and IFN-␥ secretion (15). Administration of GSI in vivo delayed the onset of EAE and substantially reduced clinical signs (15).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of T-bet is induced by signaling through TCR, IFN-␥/STAT-1, and possibly Notch (4,23). We reasoned that TLR-activated DCs could be suppressing Th2 cell development by inducing T-bet.…”
Section: Neither Up-regulation Of T-bet Expression Nor Early Suppressmentioning
confidence: 99%
“…The anti-inflammatory cytokine TGF-b 1 has previously been shown to down-regulate T-bet [14,15,20], and in some but not all instances this is mediated by SMAD proteins [21]. Minter et al [22] recently reported that murine T-bet could be regulated by the transcriptional activator Notch1 via complexes formed on its promoter. Nonetheless, neither cis nor trans regulatory elements have been clearly defined for T-BET in humans.…”
Section: Introductionmentioning
confidence: 99%